2022
DOI: 10.1093/ntr/ntac020
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic Disparities in Tobacco Retailer Density in the United States, 2000–2017

Abstract: Introduction Studies find differences in tobacco retailer density according to neighborhood sociodemographic characteristics, raising issues of social justice, but not all research is consistent. This study examined associations between tobacco retailer density and neighborhood sociodemographic characteristics in the United States (US) at four timepoints (2000, 2007, 2012, 2017) and investigated if associations remained stable over time. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…The results on income and tobacco retailer density are consistent with previous research. Higher median household income has been associated with lower tobacco retailer density in the USA10 11 33 and Scotland 16. Further, areas with a higher percentage of residents living in poverty have higher density of tobacco retailers in the USA 11 32.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The results on income and tobacco retailer density are consistent with previous research. Higher median household income has been associated with lower tobacco retailer density in the USA10 11 33 and Scotland 16. Further, areas with a higher percentage of residents living in poverty have higher density of tobacco retailers in the USA 11 32.…”
Section: Discussionmentioning
confidence: 97%
“…A number of investigations have shown that areas with lower sociodemographic composition have higher densities of tobacco retailers 10–15. The current evidence is predominantly from the USA, Australia and New Zealand.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Socio-Demographic Characteristics. Studies have shown associations between greater tobacco retail density (Kong et al, 2021;Mills et al, 2022) and lower tobacco prices (Lee et al, 2015), particularly in neighborhoods with larger proportions of Black, Hispanic/Latino, and lower-income residents. Thus, to control for the socio-demographic composition of cities, we linked retail data to 2015-2019 American Community Survey (U.S. Census Bureau, 2021a) estimates at the place level to obtain 5-year period estimates by city for median income (in U.S. dollars) and proportions (multiplied by 100%) of non-Hispanic Black and Latino populations.…”
Section: Methodsmentioning
confidence: 99%
“…Participant characteristics were compared by MTQS (low, moderate, high) using analysis of variance (ANOVA) and chi-square tests. Following each ANOVA or chi-square test, Tukey's and Bonferroni adjustments were applied (respectively) to post-hoc comparisons ( Mills et al., 2022 ; Rothman, 1990 ) in order to identify differences across high-to-low, moderate-to-low, and moderate-to-high motivation groups. A multivariate ordinal logistic regression (OLR) analysis with stepwise selection was conducted to evaluate all variables that were significantly associated with MTQS ( p ’s<0.05) together in a single model.…”
Section: Methodsmentioning
confidence: 99%